2006
DOI: 10.1207/s15324834basp2804_4
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Shift Among High-Exposure Survivors of the September 11th Terrorist Attacks

Abstract: Potentially traumatic events evoke a wide range of responses and outcomes. From a motivated social cognitive approach to ideology, system-threatening events such as 9/11 should increase psychological needs to manage uncertainty and threat and, therefore, the appeal of politically conservative opinions. We investigated "conservative shift" among high-exposure survivors of the 9/11 terrorist attacks (n = 45) and its relationship to coping and adjustment. Results indicated that Democrats and Independents (as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
259
3
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(278 citation statements)
references
References 46 publications
13
259
3
3
Order By: Relevance
“…Short-term and long-term changes stemming from the attacks may help us understand how common citizens react to the stress and threat of mass terrorism. Following 9/11, researchers found heightened levels of posttraumatic stress across the country (1), especially close to the New York attacks (2), as well as increases in individuals' trust in government (3) and conservative political attitudes (4). Heightened levels of stress and threat are linked to authoritarian political attitudes (5)(6)(7).…”
mentioning
confidence: 99%
“…Short-term and long-term changes stemming from the attacks may help us understand how common citizens react to the stress and threat of mass terrorism. Following 9/11, researchers found heightened levels of posttraumatic stress across the country (1), especially close to the New York attacks (2), as well as increases in individuals' trust in government (3) and conservative political attitudes (4). Heightened levels of stress and threat are linked to authoritarian political attitudes (5)(6)(7).…”
mentioning
confidence: 99%
“…Research suggests that high-intensity exposure to the attacks resulted in a general conservative shift and a desire for revenge among a sample of New Yorkers, regardless of the survivor's political ideology (Bonanno & Jost, 2006). More generally, results of a three-wave study with undergraduates before and after the 9/11 attacks indicated that positive attitudes towards war were greater on September, 20, 2001 compared to one year prior, although these attitudes returned to baseline within one year (Carnagey & Anderson, 2007).…”
Section: The Present Researchmentioning
confidence: 96%
“…These studies have shown that terrorist events -when defined as being serious threats to national security -usually promote support for military actions. Furthermore, many scholars (Bonanno & Jost, 2006;Crowson, DeBacker, & Thoma, 2005;Heaven, Organ, Supavadeeprasit, & Leeson, 2006;McFarland, 2005) have pointed out the effect of both Right-Wing Authoritarianism (RWA) and Social Dominance Orientation (SDO) in predicting attitudes related to the use of military aggression as part of the war on terror. RWA is defined as the covariation of three attitudinal clusters: submission to authority, aggression against conventional targets, and conventionalism (Altemeyer, 1996).…”
Section: Terrorism and The War On Terrorismmentioning
confidence: 99%
“…RWA is defined as the covariation of three attitudinal clusters: submission to authority, aggression against conventional targets, and conventionalism (Altemeyer, 1996). SDO identifies "a general attitudinal orientation toward intergroup relations, reflecting whether one generally prefers such relations to be equal versus hierarchical" (Pratto, Sidanius, Stallworth, & Malle, 1994, p. 742 Bonanno and Jost (2006) demonstrated that RWA was positively associated with support for the war in Afghanistan.…”
Section: Terrorism and The War On Terrorismmentioning
confidence: 99%